(untitled) (Comprehensive Journal of Science, 2025)
The study aimed to measure the impact of professional ethics on the reliability of internal auditing at Al-Zawiya Oil Refining Company, by assessing the effect of independence, integrity, confidentiality, and professional competence on the results of internal auditing. For this purpose, a questionnaire consisting of five sections was designed and distributed to the accountants and auditors at the Al-Zawiya Oil Refining Company, totaling 40 forms. A total of 32 were retrieved and analyzed, representing a retrieval rate of 80%, which indicates the seriousness of the respondents in dealing with the questions. To analyze this data, the Statistical Package for the Social Sciences (SPSS) programs were used to reach a set of results, which confirmed that there is an effect of adherence to professional ethics in enhancing the reliability of internal auditing at Al-Zawiya Oil Refining Company, through integrity, confidentiality, objectivity, and professional competence.